2007
DOI: 10.1002/j.2050-0416.2007.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Identify the Low Molecular Feruloylated Oligosaccharides in Beer

Abstract: Ferulic acid (4-hydroxy-3-methoxycinnamic acid), predominantly in ester form in arabinoxylan chains, is the main phenolic acid present in barley and malt. Only about 1% of the total ferulic acid in barley is present in the free form. A number of previous works concerned the contents of free and esterified ferulic acid in a broad range of popular beers, but there is little information about the possible composition of feruloylated oligosaccharides in beers. The aim of this preliminary work was to purify the fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(69 reference statements)
0
5
0
1
Order By: Relevance
“…The qualitative analyses of isolated fractions from the beer revealed that the fractions contained ferulic acid in the ester form (as proven after mild alkaline hydrolysis). It was also shown that the molecular masses of the oligosaccharides present in the purified beer fractions were similar to the masses of arabinose and xylooligosaccharides in the range of xylose to xylohexaose (Szwajgier et al 2007).…”
Section: Quantification Of Oligosaccharidesmentioning
confidence: 83%
“…The qualitative analyses of isolated fractions from the beer revealed that the fractions contained ferulic acid in the ester form (as proven after mild alkaline hydrolysis). It was also shown that the molecular masses of the oligosaccharides present in the purified beer fractions were similar to the masses of arabinose and xylooligosaccharides in the range of xylose to xylohexaose (Szwajgier et al 2007).…”
Section: Quantification Of Oligosaccharidesmentioning
confidence: 83%
“…Also, a new flavanol glucoside was identified by NMR in barley and in malt as part of the phenolic fraction of beer, known to influence several stages of brewing and beer stability. More recently, antioxidant feruloylated oligosaccharides (esterified ferulic acid attached to arabinoxylan chains) have been purified from beer and characterized by 1 H NMR …”
Section: Assessment Of Beer Composition By Nmr Spectroscopymentioning
confidence: 99%
“…In addition, the invaluable ability of NMR spectroscopy to provide compound structural information has been extensively exploited in the identification and characterization of a wide range of beer components. Targeted NMR studies have aimed at identifying and characterizing specific compounds or families of compounds, in extracts obtained from beer or raw materials, such as hop extracts and barley and barley malt extracts …”
Section: Introductionmentioning
confidence: 99%
“…Za prekurzory těchto aromatických alkoholů jsou pokládány kyseliny p-kumarová, sinapová a zejména kyselina ferulová [14]. V obilném zrnu jsou tyto látky vázány ve formě esterů nebo glykosidicky ve formě ferulovaných oligosacharidů [15]. I když byl pozorován nárůst obsahu 4-vinylguajakolu termickým štěpením při výrobě barevných sladů [16], za příčinu jeho vyššího obsahu v pivu je pokládána ferulylesterá-zová aktivita kvasinek Saccharomyces cerevisiae [17].…”
Section: Aromatické Alkoholy Jejich Vznik Výskyt a Významné Senzoriunclassified
“…Sinapic, p-coumaric, and especially ferulic acid are considered the precursors of these aromatic alcohols [14]. In grains, these substances are bonded in the form of esters or glycosidically in the form of feruloylated oligosaccharides [15]. Although an increase in 4-vinylguaiacol content was observed during thermal fission when producing coloured malts [16], feruloyl esterase activity of yeast Saccharomyces cerevisiae is considered to be the cause of its higher content in beer [17].…”
Section: Aromatic Alcohols Their Formation Presence and Significantmentioning
confidence: 99%